2023
DOI: 10.3389/fgene.2023.1114650
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of vitrification on the transcriptome of human ovarian tissue in patients with gynecological cancer

Abstract: Objective: This study investigated the effects of a vitrification/warming procedure on the mRNA transcriptome of human ovarian tissues.Design: Human ovarian tissues were collected and processed through vitrification (T-group) and then subjected to RNA sequencing (RNA-seq) analysis, HE, TdT-mediated dUTP nick-end labeling (TUNEL), and real-time quantitative PCR, and the results were compared to those of the fresh group (CK).Results: A total of 12 patients, aged 15–36 years old, with a mean anti-Müllerian hormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Other pathways associated with reproduction are the ECM-receptor interaction, focal adhesion, and Jak-STAT. Gu et al [53] demonstrated that the cryopreservation process can activate or deactivate these physiological functions. However, once ovarian grafts were able to support complete oocyte growth, the dysregulation of genes could be associated with a compensatory mechanism to maintain ovarian viability after vitrification, which qualitatively did not impair oogenesis.…”
Section: Ovarian Tissue Thawing and Transplantationmentioning
confidence: 99%
“…Other pathways associated with reproduction are the ECM-receptor interaction, focal adhesion, and Jak-STAT. Gu et al [53] demonstrated that the cryopreservation process can activate or deactivate these physiological functions. However, once ovarian grafts were able to support complete oocyte growth, the dysregulation of genes could be associated with a compensatory mechanism to maintain ovarian viability after vitrification, which qualitatively did not impair oogenesis.…”
Section: Ovarian Tissue Thawing and Transplantationmentioning
confidence: 99%
“…In general, cryopreservation of ovarian tissue can result in changes in gene expression and protein abundance at different stages [ 48 , 49 ]. More precisely, cryopreservation also hampers several specific epigenetically relevant factors ( Table 1 ).…”
Section: Otc and The Epigenomementioning
confidence: 99%
“…Interestingly, a recently published systematic review and meta-analysis has reported a significantly greater proportion of intact stromal cells in vitrified tissue versus slow-frozen tissue, with no significant differences with respect to the proportion of intact primordial follicles, extent of DNA fragmentation, or mean primordial follicle density [20]. Conversely, some reports suggested that vitrification may induce changes in mRNA expression and delayed growth of follicles in vitro in human ovarian tissues [21,22].…”
Section: Ovarian Tissue Cryostoragementioning
confidence: 99%